PENERAPAN LEMBAR KEGIATAN SISWA INKUIRI PADA MATERI DAUR ULANG LIMBAH KELAS X DI SMA NEGERI 1 MANYAR GRESIK UNTUK MENINGKATKAN KETUNTASAN HASIL BELAJAR SISWA - RESTI ABRIYANTI (Berkala Ilmiah Pendidikan Biologi (BioEdu), 2013)
The objective of this research is to determine the completeness of students learning outcomes. This research uses One-Shot Case Study Method. The one shot case study method is pre-experimental research, because it doesn’t use control class. In this research showed that 83,33% of students complete the learning outcomes. Performance of students categorized as very good. The ability of teacher to manage learning, increases in every meeting. The dominant activity of the students at the first meeting is create groups based on instructions from the teacher, with the percentage of 14,33%. The second meeting is doing experiment according to the design and procedure, with percentage of 12%. Student’s response to the use of Inquiry Student’s Worksheet categorized as very good.     Keywords: Student Worksheet, Inquiry, Waste Recycling.